The Phonograms’ Genuine‐Character Status: What the Embedded Semantic Radicals’ Semantic Activation Live by - Meng Jiang; Ya Tan; Xia Wang; Yuli Hao (Brain and Behavior)
ABSTRACT Background In Chinese phonogram processing studies, it is widely accepted that both character and non‐character semantic radicals could be semantically activated. However, little attention was paid to the underlying workings that enabled the semantic radicals’ semantic activation. Purpose The present study aimed to address the above issue by conducting two experiments. Methods Experiment 1 was committed to confirming whether both character and non‐character semantic radicals could be semantically activated when embedded in genuine Chinese phonograms. Experiment 2 was devoted to exploring whether the same semantic radicals could also be semantically activated when incorporated in Chinese pseudo‐characters. Results Results demonstrated that both character and non‐character semantic radicals embedded in the genuine phonograms were semantically activated, but those placed in the pseudo‐characters underwent no semantic activation, suggesting that the semantic activation of semantic radicals was genuine‐character status‐dependent, irrespective of the semantic radicals’ characterhood. Conclusion It seems that the genuine‐character status and the meaning of the host phonogram have strong sway on the semantic activation of semantic radicals.